Clinical Handbook of Chinese Medicine - Xu, Bob (World Scientific Publishing Company, 2014)
"This is a concise handbook providing a quick clinical reference on Chinese medicinal treatments for many diseases, based on traditional Chinese medicine theory and practice. Organized by different clinical conditions and diseases, it provides clinicians and healthcare professionals with definitions and recommended treatment methods, especially herbal medicine formulae. In addition to being a comprehensive quick reference source, this handbook also conveys a generalized understanding of Traditional Chinese Medicine"--EBL